2018
DOI: 10.4187/respcare.05869
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Awareness of the Roles, Knowledge, and Skills of Respiratory Therapists Through an Interprofessional Education Experience

Abstract: IPE improved student knowledge in the roles and responsibilities competency domain. In particular, nursing and occupational therapy students became more aware of the knowledge and skill set of the RT profession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…This investigation revealed positive perception changes in Roles and Responsibilities that align with previous investigations using a variety of outcome measures (Arenson et al, 2015;McGehee et al, 2018;McLeod et al, 2014;Zamjahn et al, 2018); contrasting results also exist (Soubra et al, 2018). Consistent with our findings, Teamwork skills were found to be enhanced in undergraduate health professions students following online and face-to-face IPE activities (McLeod et al, 2014;Packard et al, 2016;Soubra et al, 2018;Zanotti et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…This investigation revealed positive perception changes in Roles and Responsibilities that align with previous investigations using a variety of outcome measures (Arenson et al, 2015;McGehee et al, 2018;McLeod et al, 2014;Zamjahn et al, 2018); contrasting results also exist (Soubra et al, 2018). Consistent with our findings, Teamwork skills were found to be enhanced in undergraduate health professions students following online and face-to-face IPE activities (McLeod et al, 2014;Packard et al, 2016;Soubra et al, 2018;Zanotti et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…The experiences obtained from interprofessional simulations have been mostly positive (Costello et al, 2018;Ivey, Bowman, & Lockeman, 2018;Jakobsen et al, 2018;Popkess et al, 2017;Roberts & Goodhand, 2018;Zamjahn et al, 2018), and there have been few differences in the participants' satisfaction levels based on different occupational groups or sectors. However, in a study by Jakobsen et al (2018), medical students were found to learn more than nursing students about the leader's role during a simulation.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The participants have found that the simulations have increased their confidence in their own skills (Hovland et al, 2018;Jakobsen et al, 2018;Smith et al, 2018) and helped them prioritize patient needs (Roberts & Goodhand, 2018;Smith et al, 2018). Simulations have also allowed the participants to increase their understanding of the roles and responsibilities of other professionals (Bradway et al, 2018;Costello et al, 2018;Pinto et al, 2018;Wietholter et al, 2017;Zamjahn et al, 2018). Furthermore, interprofessional simulations have developed the participants' leadership skills (Jakobsen et al, 2018;Pinto et al, 2018) and improved their stress management ability (Jakobsen et al, 2018).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Zamjahn et al 2 have provided more evidence that IPE can be successfully implemented into respiratory therapy curriculum by using interprofessional clinical simulation. Clinical simulation is one of several different models that can facilitate IPE, with evidence supporting its use in addressing the collaborative practice competencies established by the IPE Collaborative Expert Panel.…”
Section: Creating a Collaborative Practice-ready Professionmentioning
confidence: 99%
“…Clinical simulation is one of several different models that can facilitate IPE, with evidence supporting its use in addressing the collaborative practice competencies established by the IPE Collaborative Expert Panel. 2,15 The use of IPE can further support the development of skills and practices that address competencies needed by respiratory therapists. The collaborative practice competencies of team and teamwork, roles and responsibilities, communication, and values/ethics 16 can be found embedded in the respiratory care competency areas of leadership and disease management, 12 which provide a framework to help us achieve a competent and collaborative practice-ready profession.…”
Section: Creating a Collaborative Practice-ready Professionmentioning
confidence: 99%